2015
DOI: 10.1007/s10973-015-5153-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of various carbon nanofillers on the thermal properties of paraffin for energy storage applications

Abstract: The addition of carbon nanofillers to phase change materials (PCMs) has received much attentions recently. The shape effects of carbon nanofillers on the thermal properties of paraffin were investigated in this work. Four types of nanocomposite PCMs were prepared by mixing paraffin with multi-wall carbon nanotubes (MWCNTs), graphitized MWCNTs, nanographene with different layer numbers (GNP-B, GNP-C). It shows that phase change enthalpy of nanocomposite PCM decreases gradually with the increasing of the loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As reported in a previous study by Wu et al 34 first the paraffin was melted at 90° and then the MWCNTs were added to the molten paraffin. Premixing was done by a magnetic stirrer for 15 minutes, and final stage of mixing was done by an ultrasound mixer until a homogeneous solution was formed.…”
Section: Methodsmentioning
confidence: 99%
“…As reported in a previous study by Wu et al 34 first the paraffin was melted at 90° and then the MWCNTs were added to the molten paraffin. Premixing was done by a magnetic stirrer for 15 minutes, and final stage of mixing was done by an ultrasound mixer until a homogeneous solution was formed.…”
Section: Methodsmentioning
confidence: 99%
“…Zeng et al (2008) added Ag nanoparticles to myristyl alcohol, and the thermal conductivity increased with the increase of Ag nanoparticles, and the phase transition temperature and latent heat decreased slightly. Wu et al (2016) prepared nanocomposite PCM by mixing paraffin with multi-walled carbon nanotubes (MWCNTs). The results showed that as the loading of carbon nanofillers increased, the thermal conductivity of the nanocomposite PCM increased, and the phase change enthalpy gradually decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al [19] added Ag nanoparticles to myristyl alcohol, and the thermal conductivity increased with the increase of Ag nanoparticles, and the phase transition temperature and latent heat decreased slightly. Wu et al [20] prepared nanocomposite PCM by mixing paraffin with multiwalled carbon nanotubes (MWCNTs). The results showed that as the loading of carbon nanofillers increased, the thermal conductivity of the nanocomposite PCM increased, and the phase change enthalpy gradually decreased.…”
Section: Introductionmentioning
confidence: 99%